2017
DOI: 10.1016/j.ecoenv.2016.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Geno- and cytotoxicity induced on Cyprinus carpio by aluminum, iron, mercury and mixture thereof

Abstract: Metals such as Al, Fe and Hg are used in diverse anthropogenic activities. Their presence in water bodies is due mainly to domestic, agricultural and industrial wastewater discharges and constitutes a hazard for the organisms inhabiting these environments. The present study aimed to evaluate geno- and cytotoxicity induced by Al, Fe, Hg and the mixture of these metals on blood of the common carp Cyprinus carpio. Specimens were exposed to the permissible limits in water for human use and consumption according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 85 publications
0
7
0
1
Order By: Relevance
“…Diverse studies have shown that exposure to high concentrations of Al can trigger a wide range of toxicity mechanisms in different animal models (Martínez-vieyra et al, 2017;Mathiyazahan et al, 2015;Ward et al, 2006). In aquatic organisms environmental exposure to Al has been related to embryolethality and teratogenic effects (Kovrižnych et al, 2013;Monaco et al, 2017), neurotoxicity (Monaco et al, 2017), geno-cytotoxicity and congenital malformations (Gómez-Oliván et al, 2017;Quiroga-Santos et al, 2021), morphological and behavioral alterations (Grassie et al, 2013;Griffitt et al, 2008) , iono and osmo regulatory disturbances (Kumar and Gill, 2014) and oxidative stress (González-González et al, 2014;Razo-Estrada et al, 2013).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Diverse studies have shown that exposure to high concentrations of Al can trigger a wide range of toxicity mechanisms in different animal models (Martínez-vieyra et al, 2017;Mathiyazahan et al, 2015;Ward et al, 2006). In aquatic organisms environmental exposure to Al has been related to embryolethality and teratogenic effects (Kovrižnych et al, 2013;Monaco et al, 2017), neurotoxicity (Monaco et al, 2017), geno-cytotoxicity and congenital malformations (Gómez-Oliván et al, 2017;Quiroga-Santos et al, 2021), morphological and behavioral alterations (Grassie et al, 2013;Griffitt et al, 2008) , iono and osmo regulatory disturbances (Kumar and Gill, 2014) and oxidative stress (González-González et al, 2014;Razo-Estrada et al, 2013).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Many studies have reported synergistic effects from the combination of toxicants. For example, the combination of Al and Hg as well as the combination of As and Pb have been shown to result in synergistic effects (Pohl et al 2011, Gómez-Oliván et al 2016). As such, the issue of multiple exposures and how they could possibly influence gender-specificity is another limitation of this current examination.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Дефекти ERCC1залежної активності призводять до геномної нестабільності та знижують життєздатність клітин. Генотоксичність впливу ртуті була продемонстрована в клітинах крові звичайного коропа (Gómez-Oliván et al, 2017). Однак вплив неорганічної ртуті на системи відновлення ДНК у мозку риб досі не були представлені у літературі.…”
Section: результати та їх обговоренняunclassified